Analysis of Environmentally Friendly Fishing Equipment in Pasar Bantal Village Teramang Jaya District Mukomuko Regency - Nuanzha, Sissy Femi; Zamdial, Zamdial; Hartono, Dede (Jurnal Kelautan dan Perikanan Indonesia, 2022)
Environmentally friendly fishing gear is a fishing gear that does not have a negative impact on the environment, such as not damaging the bottom of the water. There are 4 fishing gears that are often used by the people of Pasar Pillow Village, Teramang Jaya District, namely longline fishing rods, shrimp trawls, millennium nets and nylon nets. Research on the analysis of environmentally friendly fishing gear was carried out in April May 2022 in Pasar Pillow Village, Teramang Jaya District, Mukomuko Regency. This study aims to analyze environmentally friendly fishing gear (API) in Pasar Pillow Village, Teramang Jaya District, Mukomuko City. The method used is the survey method. Collecting data using observation, interviews and documentation methods. The results of the research data were analyzed by descriptive method. The categories of environmentally friendly fishing gear used by Pillow Market fishermen are longline fishing rods, nylon nets, and millennium nets. The fishing gear that is not environmentally friendly is the shrimp trawl.Keywords: Fishing gear, environmentally friendly, Pasar Bantal Village, Mukomuko